Yearbook of the European Convention on Human Rights/Annuaire de la convention europeenne des droits de l'homme, Volume 44 (2001) (Human Rights and Humanitarian Law - Book Archive 2000-2005., 2002)
This volume of the Yearbook of the European Convention on Human Rights , prepared by the Directorate of Human Rights of the Council of Europe, relates to 2001. Its presentation follows that of previous volumes. Part one contains basic texts and information of a general nature; part two deals with the European Commission of Human Rights; part three with the European Court of Human Rights; part four with the Resolutions of the Committee of Ministers; and parts five and six with the other work of the Council of Europe in the field of human rights, the situation in the Member States, and developments within the European Communities. A bibliography and index are included.